Amaranth cultivation in Kenya - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1986)
Three varieties of amaranth, developed and tested at the University of Nairobi, have been given to peasant farmers to cultivate. Native to South America, this plant is now receiving renewed attention and considerable research is being undertaken,...